2017
DOI: 10.1136/oemed-2017-104375
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels, iron metabolism gene polymorphisms and homocysteine: a gene-environment interaction study

Abstract: Blood lead levels were positively associated with plasma homocysteine levels measured 4-6 years later, and three SNPs in the gene modified the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…All studies of this review support that Pb concentrations are correlated with high levels of Hc [9,[21][22][23][24][25][26][27][28][29][30].…”
Section: Lead (Pb)mentioning
confidence: 74%
See 4 more Smart Citations
“…All studies of this review support that Pb concentrations are correlated with high levels of Hc [9,[21][22][23][24][25][26][27][28][29][30].…”
Section: Lead (Pb)mentioning
confidence: 74%
“…Kim et al [22], in a population-based cohort, found an association between Pb and Hc concentrations in people living in South Korea. Furthermore, Kim reported, in the framework of genotypes for the target gene single-nucleotide polymorphisms analysis, that people with variant alleles in the transferrin gene showed a positive correlation with Pb and Hc increased levels.…”
Section: Lead (Pb)mentioning
confidence: 97%
See 3 more Smart Citations